PENGARUH IKLAN ONLINE PADA FACEBOOK TERHADAP KEPUTUSAN PEMBELIAN PAKAIAN (Studi pada Mahasiswa Politeknik Mandiri Bina Prestasi) - Sitorus, Olga Theolina (Fakultas Ekonomi Universitas Negeri Medan, 2024)
This study was conducted to determine how far the influence of consumer attitudes on online advertising, consumer memory on online advertising and the frequency of consumer clicks on Facebook media online advertisements can influence consumer purchasing decisions. The population in this study were all students at Bina Prestasi Independent Polytechnic, totaling 444 people. Sampling using the slovin formula. From a population of 444, 81 people were selected as samples in this study. Research data obtained through questionnaires distributed by google form and literature study. Data analysis using multiple linear regression analysis techniques. Some of the analytical methods used are descriptive methods, Likert scale and instrument validity testing. The results showed that consumer attitudes, consumer memory and consumer click frequency had a simultaneous and significant effect on consumer purchasing decisions. Then partially consumer attitudes and consumer memory have a significant effect on purchasing decisions. However, the variable frequency of consumer clicks has no effect on consumer purchasing decisions. This can be seen from the results of the analysis that consumers rarely click on online advertisements that appear on the Facebook media, some consumers click on online advertisements only because they have bought before, and if they have seen the same advertisement many times on the Facebook media even though they have never bought it before, they will click on it.Keywords: attitude, recall, click frequency, consumer purchasing decisions.